LEGAL SOCIOLOGY OF LAND CONFLICT VS ORANG RIMBA’S LAND CONFLICT IN JAMBI PROVINCE - Ulma, Riri Oktari; Rahmi, Elita; Fitria, Fitria; Pratiwi, Cholillah Suci (Pusat Unggulan Ipteks-PUI Universitas Jambi, 2023)
The sociology of Orang Rimba Law, which portrays the issue of land conflict versus land conflict, is a crucial legal issue, even though so far, the Orang Rimba (Suku Anak Dalam) has been part of a beneficial symbiosis between Natural Resources and Human Resources (HR), because between the factors of mutual care between humans and nature, but in legal reality, land and land tenure in Indonesia,Â The existence of the Orang Rimba institution as the original entity of the Malay tribe is a problem, because its living entity has been displaced by the laws of outsiders, namely the state and government, especially since the rolling of the issue of forest utilization through Forest Tenure Rights (HPH) and the use of forest products through legal entities whose ownership is by forest outsiders, plus natural disasters (forest fires) outsiders as people whom people have long feared as eating creatures human. The purpose of the study is to know the law in reality, especially society. Conclusion The Orang Rimba, as an indigenous entity in Jambi Province, must be brought to the attention of the local government. The right to life and other social rights, namely distinctive economic and cultural rights, must be fostered continuously so that their customary rights are protected from land grabs under the guise of plantations and forestry based on state approval of forests and non-forests and ignore the history of the Orang Rimba struggle which always maintains the forest ecosystem and its distinctive land and culture such as ritual rituals between man and nature to dispel nature's various kinds of anger against humans in the form of disasters, wrath, and even climate change, cultural mantras and dialects were developed by them, but have not been seen by Indonesian law as genuine and distinctive legal institutions.